Natriuretic peptides: molecular biology, pathophysiology and clinical implications for the cardiologist. (July 2013) - D'Alessandro, Raffaella; Masarone, Daniele; Buono, Andrea; Gravino, Rita; Rea, Alessandra; Salerno, Gemma; Golia, Enrica; Ammendola, Ernesto; Del Giorno, Giuseppe; Santangelo, Lucio; Russo, Maria Giovanna; Calabrò, Raffaele; et al.
Natriuretic peptides (NPs) counter the effects of volume overload or adrenergic activation of the cardiovascular system. They are able to induce arterial vasodilatations, natriuresis and diuresis, and they reduce the activities of the renin–angiotensin–aldosterone system and the sympathetic nervous system. However, in addition to wall stress, other factors have been associated with elevated natriuretic peptide levels. Since 2000, because of their characteristics, NPs have become quantitative plasma biomarkers of heart failure. Nowadays, NPs play an important role not only in the diagnosis of heart failure, but also for a prognostic purpose and a guide to medical therapy. Finally, a new drug that modulates the NP system or recombinant analogs of NPs are now available in patients with heart failure.